Chemotherapy‐induced thrombocytopenia in Ewing sarcoma: Implications and potential for romiplostim supportive care. Issue 7 (28th December 2021) - Merjaneh, Nawal; Young, Jennifer; Mangoli, Avani; Olsen, Mallery; Setty, Bhuvana; Lane, Adam; Nagarajan, Rajaram; Pressey, Joseph G.; Turpin, Brian
Abstract: Background: Maintaining dose‐dense, interval‐compressed chemotherapy improves survival in patients with Ewing sarcoma but is limited by myelosuppression. Romiplostim is a thrombopoietin receptor agonist that may be useful in the treatment of chemotherapy‐induced thrombocytopenia (CIT). Methods: Patients aged between 3 and 33 years with Ewing sarcoma from 2010 to 2020 were reviewed. CIT was defined as a failure to achieve 75, 000 platelets per microliter by day 21 after the start of any chemotherapy cycle. Fisher's exact test was used for univariate analysis and Pearson's correlation coefficient was used for the association between continuous variables. Results: Twenty‐seven out of 42 patients (64%) developed isolated CIT, delaying one to four chemotherapy cycles per patient. CIT occurred during consolidation therapy in 24/27(88.9%) and with ifosfamide/etoposide cycles in 24/27 (88.9%). Univariate analysis failed to identify risk factors for CIT. The use of radiation approached significance ( p ‐value = .056). Ten patients received romiplostim. The median starting dose was 3 μg/kg (range 1–5). Doses were escalated weekly by 1–2 to 4–10 μg/kg and continued throughout chemotherapy. A higher romiplostim dose was associated with a higher change in average platelet counts from baseline, r  = .73 ( p  = .04). No romiplostim‐related adverse events were identified aside from mild headache. Conclusions: CIT is the primary reason for the inability to maintain treatment intensity in Ewing sarcoma. The concurrent use of romiplostim with chemotherapy was safe and feasible, and efficacy was associated with higher romiplostim doses.